Infrastructural development and poverty reduction in Java, Indonesia 2002-2012 - Prawesti, Puspita Ayuningtyas (JPAS (Journal of Public Administration Studies), 2017)
Research on the linkage between the infrastructural development and poverty reduction has not expanded as the studies on the impact of infrastructural development towards economic growth yet Indonesian government takes the infrastructural construction as one of main policies to eradicate poverty. Therefore, this paper attempts to examine whether the infrastructural development is an effective policy to reduce the poverty incidence in Java Island, Indonesia, the homes of the most number of poor people in within the nation compared to other major islands. Panel data regression was performed by using the macroeconomic data in Java Island from 2002-2012 to answer such question. The statistical results proves that household access to basic infrastructures more significantly contribute to poverty alleviation than the government expenditures for specific allocation that in some parts used for the enhancement of infrastructure. Surprisingly, the government expenditure for infrastructure increases the poverty prevalence within the island. The policy recommendation that can be proposed from this research is that the government should formulate more effective mechanism to make the government expenditure an effective tool to alleviate poverty and increase the percentage of budget sharing to sub-national level within the framework of fiscal decentralization.